Analysis and Evaluation of the Android Best Practices Impact on the Efficiency of Mobile Applications - Tonini, Aline Rodrigues; Fischer, Leonardo Matthis; Mattos, Júlio Carlos Balzano de; Brisolara, Lisane Brisolara de (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2013: Anais do III Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2013)
This paper evaluates the impacts of two most promising Android best practices regarding performance and energy consumption. In the experiments, the practices are applied to the code of an Android application and the code efficiency on different mobile devices is analyzed. Experimental results indicate that the use of the most appropriate for syntax and the avoiding getters/setters improves the Android codes efficiency.